Singapore's water challenges past to present. Issue 2 (3rd March 2020) - Ng, Peter Joo Hee; Teo, Celine
ABSTRACT: Problems with drought, floods and public sanitation are commonplace for any developing country. The manner in which Singapore has overcome these difficulties, however, may well be exceptional. Water scarcity was, is, and remains a trial for Singapore's decision makers. Singapore's water management method is distinguished by three qualities: integration, circularity and the taking of an uncommonly long view. Thus, despite nature's poor endowment, today's Singapore is not short of water. This is possible only because it has been realistic about its circumstances, and has used its intellect and imagination, researching continuously, and continues to muster the will to pursue hard-nosed water policies.